2005
DOI: 10.1186/1471-2415-5-23
|View full text |Cite
|
Sign up to set email alerts
|

Citalopram associated with acute angle-closure glaucoma: case report

Abstract: Background: Acute angle-closure glaucoma is a rare complication in patients receiving antidepressant treatment. In the following case, we report the development of acute angle closure glaucoma in a patient who overdosed on Citalopram, an antidepressant, and discuss the possible etiological mechanisms for the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…56,57 The cause of ACAG in other groups of antidepressants is induced mydriasis by anticholinergic action of these medications in patients with narrow iridocorneal angle. Of tricyclic agents, amitryptiline (the most commonly reported agent) and imipramine 58 and of the non-tricyclic drugs, mianserin hydrochloride, 59 paroxetine, 57,60 fluoxetine, 61 maprotiline, 62,63 fluvoxamine, 64 venlafaxine, 65,66 citalopram, 67 and escitalopram 68 have been documented to be associated with ACAG attacks. Ritch et al 58 reported development of ACAG in four patients with occludable angles who received routinely prescribed doses of imipramine.…”
Section: Antidepressantsmentioning
confidence: 99%
“…56,57 The cause of ACAG in other groups of antidepressants is induced mydriasis by anticholinergic action of these medications in patients with narrow iridocorneal angle. Of tricyclic agents, amitryptiline (the most commonly reported agent) and imipramine 58 and of the non-tricyclic drugs, mianserin hydrochloride, 59 paroxetine, 57,60 fluoxetine, 61 maprotiline, 62,63 fluvoxamine, 64 venlafaxine, 65,66 citalopram, 67 and escitalopram 68 have been documented to be associated with ACAG attacks. Ritch et al 58 reported development of ACAG in four patients with occludable angles who received routinely prescribed doses of imipramine.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Pharm Biomed Res 2017; 3(3): 32 paroxetine(9-13),citalopram (3,14), escitalopram (15),and sertraline (7). Recently, Lochhead has reported five cases of optic neuropathy in patients treated with paroxetine for 14 years(one case), citalopram for three and 10 years(two cases), fluoxetine for five years(one case), sertraline for six months and citalopram for six months(one case) (16).In most of the cases mentioned above, ocular complications of SSRIs occurred in women more than 50 years old and with underlying medical illness, and treated with drugs other than antidepressants (17).…”
Section: Pharmaceutical and Biomedical Researchmentioning
confidence: 99%
“…It is widely used in treating patients with anxiety, depression, or other types of heterogenic mood disorders (1). In the last two decades, mood disorders have developed to an impressive extent and the prescription of SSRIs has increased because of its safety and tolerable profile in comparison with other antidepressant drugs (2)(3)(4)(5).Ocular complications of SSRIs are rarely detected and can be accompanied by dangerous consequences (6).Short-term SSRI exposure causes pupillary dilator muscle stimulation, active mydriasis, a sudden blockage of the drainage of aqueous humor fluid out of the eyes, a rapid rise in the intraocular pressure (IOP) level, damage to the optic nerve at the back of the eye,ultimately leading to acute angle closure glaucoma(AACG) (7). AACG is an ocular emergency and requires immediate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…One of the cases is an alcoholic woman used overdose of citalopram and the other is described as a patient using citalopram regularly. 58,59 In literature, ACG related with escitalopram is described in one case. The use of escitalopram in a 41 year old woman caused rotation in anterior chamber angle as a result of uveal effusion and development of acute bilateral ACG.…”
Section: Antidepressants Tricyclic Antidepressant Agents (Tcas)mentioning
confidence: 99%
“…While 6 of these are related with paroxetine, 2 are citalopram, one is escitalopram, one is Fluoexetine, one is Fluvoxamine, there is not case notified on sertraline. 38,44,50,58,59,60 For this reason, paroxetine is responsible for most of the glaucoma cases. 38 In three of the six cases paroxetine is identified in geriatric patients (aged between 70-91), 2 of the cases are used in young patients who are hypermetropic and plateau iris configuration is identified in one patient.…”
Section: Antidepressants Tricyclic Antidepressant Agents (Tcas)mentioning
confidence: 99%